The Correlation of Learning Motivation and Conventional Learning Methods with Civic Education Learning Outcomes - Maharani, Indah; Dabutar, Nabila Febriyanti; Ingtyas, Fatma Tresno; Ginting, Laurena (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study examines the relationship between learning Motivation and conventional teaching methods on students' learning outcomes in Civic Education. The research employed a quantitative approach with a correlational design. Data were collected through questionnaires designed to measure learning motivation, applying conventional teaching methods, and students' learning outcomes. Data analysis was conducted using simple linear regression and correlation analysis. The results revealed a significant positive relationship between learning Motivation and students' learning outcomes and a significant relationship between conventional teaching methods and students' outcomes. Learning Motivation enhances student engagement, enthusiasm, and overall learning quality. Meanwhile, while effective, conventional teaching methods can be further enhanced by integrating interactive approaches such as group discussions or visual media. The implications of this study highlight the need for teachers to design teaching strategies that are relevant to students' needs and capable of continuously motivating them. A combination of strong learning motivation and optimal implementation of conventional teaching methods is believed to effectively support students' academic success. Therefore, these factors should primarily focus on developing school learning strategies for better outcomes.